Emotions and 21st Century Communication - Niket, Mehta; Suparna, Dutta (International Journal of Engineering and Technology, 2018)
Electronic Media is no more a buzz word now. Almost every educated and semi-educated person all over the world is a part of digital media and access information electronically. Affordable smart phones, electronic gadgets and telecommunication services have made communication fast and multimedia-rich containing text, images, audio-video and animation messages. In this 21st century, digital media has given a democratic opportunity to all of us to become a broadcaster. People discuss online about issues of considerable importance and as well as trivial matters. This online platform has brought out many changes in personality and thoughts of its users and especially of the coming generation. Sharing confidential information and being accessible 24X7 has brought out changes in behavior and manner- ism of new generation. New generation has become more expressive and communicate more than earlier generation. They are connected to more and diverse set of people all at once and every time. Communication which is always based on emotions has changed in current scenario which is the theme of this paper.Â Â